A practical approach to programming with assertions - Rosenblum, D.S. (IEEE transactions on software engineering, 1995)
Embedded assertions have been recognized as a potentially powerful tool for automatic runtime detection of software faults during debugging, testing, maintenance and even production versions of software systems. Yet despite the richness of the notations and the maturity of the techniques and tools that have been developed for programming with assertions, assertions are a development tool that has seen little widespread use in practice. The main reasons seem to be that (1) previous assertion processing tools did not integrate easily with existing programming environments, and (2) it is not well understood what kinds of assertions are most effective at detecting software faults. This paper describes experience using an assertion processing tool that was built to address the concerns of ease-of-use and effectiveness. The tool is called APP, an Annotation PreProcessor for C programs developed in UNIX-based development environments, APP has been used in the development of a variety of software systems over the past five years. Based-on this experience, the paper presents a classification of the assertions that were most effective at detecting faults. While the assertions that are described guard against many common kinds of faults and errors, the very commonness of such faults demonstrates the need for an explicit, high-level, automatically checkable specification of required behavior. It is hoped that the classification presented in this paper will prove to be a useful first step in developing a method of programming with assertions.< >